ETHIC AND SPORT - Željko Kaluđerović (Human Research in Rehabilitation, 2011)
In this paper the author considers the rules of sports (constitutive and sportsmanship rules), moral values of sports (justice, honesty, responsibility, benefi cence) and fair play. Constitutive rules are the rules which determine the essence of the game itself, determine the structure of a certain sport, standardize the way in which it is played and sanction unallowed sport activities. Sportsmanship represents unwritten moral rules based on virtues of righteousness and honesty. Moral values are predominant forms of understanding of the purpose of human activity and the way in which human moral character is practically manifested. Fair play can be defi ned as commitment to the spirit and letter of equality of competitors in relation to the rules, and all towards the common search for excellence. The author believes that the rules, moral values and fair play in sport are required for any game to become actually possible to play. Nevertheless, occasionally, the necessity of some of the above mentioned preconditions, for example sportsmanship, is being relativized. Namely, the standing point that a competitor needs to make a certain effort in order to encourage his opponent to play well, and thus raise the level of enjoyment for both himself and his opponent, does not meet either the general approval of athletes or of the public. It is generally claimed that it is suffi cient to play by the rules in order to proclaim the playing as morally correct. The author looks at such an attempt to separate the sport from morality through the prism of modern tendency to separate different forms of practical activity from their ethical implications.